A New method of simulating urban ventilation corridors using circuit theory. (August 2020) - Xie, Peng; Yang, Jun; Wang, Huiying; Liu, Yanfang; Liu, Yaolin
Highlights: Urban ventilation corridor recognition using circuit theory is proposed. The method is based on numerical simulation of ventilation corridor analysis. Wuhan urban area is analyzed using three-dimensional building data of 2015. The method can identify ventilation corridor and analyze ventilation environment. Complex aerodynamics calculations can be avoided in the proposed method. Abstract: With the continuous development of global urbanization, the urban heat island effect has increasingly become one of the important factors that reduces the quality of urban life. Among the many factors affecting the formation of urban heat islands, urban canopy ventilation is considered to have great potential for improving urban heat islands. Based on the traditional numerical simulation of ventilation corridor analysis, this paper proposes a new approach for ventilation corridor recognition based on circuit theory. The connotations of resistance, current, and voltage in the simulation of urban ventilation environment were explained separately. Taking Wuhan as the research area, local three-dimensional building data were used as the data source, and a simulation experiment of the urban ventilation environment with different winds was carried out on the 100-m grid scale. Unlike the method based on the least-cost path analysis by which only a few main ventilation corridors can be generated, the results of the method proposed in this paper cover all grid cells in the study area. The simulation results were represented by probabilistic values, which can effectively reflect the ventilation corridor and ventilation barriers. In addition to identifying the ventilation corridors, the tuyeres were also well identified.